Бронзовый нагрудник панцыря с изображением головы Медузы из кургана № 6/1914-1915 у ст. Елизаветинской в Прикубанье - Трейстер, М.Ю. (Боспорские исследования, 2009)
In 1914, during archaeological digs of the tumulus no. 6 near Elizavetinskaya place N.I. Veselovsky found a plunder’s pit with ledges. There were stone slabs of a destroyed crypt, small bronze coat of mail plates and a bronze coat of mail breastplate representing the head of Medusa in relief. The author considers the elements of ceremonial armour of late archaic - early classic period together with the one decorated with gorgoneions of early types, which could be the prototypes for armourers of the end of the 5th - the first quarter of the 4th century BC, were in use right up to the beginning of the 4th century BC. It is not improbable that the coat of mail from Elizavetinskaya, which is made in archaic style, can be related to their production. Unfortunately, the breastplate was found not in situ but in the plunder’s pit. The burial was robbed completely and there are no any data either for dating specification of the context or for the ideas on the subject of attribute of this unique armour.